2018
DOI: 10.3310/hta22410
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine preloading for smoking cessation: the Preloading RCT

Abstract: BackgroundNicotine preloading means using nicotine replacement therapy prior to a quit date while smoking normally. The aim is to reduce the drive to smoke, thereby reducing cravings for smoking after quit day, which are the main cause of early relapse. A prior systematic review showed inconclusive and heterogeneous evidence that preloading was effective and little evidence of the mechanism of action, with no cost-effectiveness data.ObjectivesTo assess (1) the effectiveness, safety and tolerability of nicotine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 71 publications
1
13
0
Order By: Relevance
“…The cyclic repetition of this mechanism during a 6-week period could have weakened the learnt association between reinforcement and smoking, facilitating cessation. This analysis is supported by the above study of Aveyard and colleagues [16], showing that changes in abstinence were mediated mainly by a reduction in the drive to smoke before and after smoking cessation, and by a reduction in smoke intake. The present findings also support…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The cyclic repetition of this mechanism during a 6-week period could have weakened the learnt association between reinforcement and smoking, facilitating cessation. This analysis is supported by the above study of Aveyard and colleagues [16], showing that changes in abstinence were mediated mainly by a reduction in the drive to smoke before and after smoking cessation, and by a reduction in smoke intake. The present findings also support…”
Section: Discussionsupporting
confidence: 66%
“…The present findings considerably strengthen the existing evidence for a unified mechanism of preloading and support the view that the benefits of pre-treatment are not specific to varenicline. In the largest trial of nicotine preloading published to date, Aveyard and colleagues [16] found an increase in long-term abstinence after 4 weeks of preloading with a nicotine patch followed by standard cessation therapy. Interestingly, in the initial analysis, the nicotine preloading benefit was undermined because it reduced the use of varenicline in the post-quit treatment; however, when the results were adjusted for the use of post-quit varenicline, the effect of nicotine preloading was larger than the unadjusted value and was statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, some medical institutions around the world have carried out autologous blood recovery from amniotic fluid in the operation field after delivery and placenta separation and filtration of white blood cells without leading to obvious puerperal complications [ 13 ]. Although the technique has been confirmed to be safe by multiple studies with large clinical sample sizes [ 14 ], its promotion has currently encountered some taboos. For example, pregnant patients with malignant tumours and patients with sickle cell anaemia were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…It increases the rate of quitting and is assumed that nicotine preloading is reasonably effective in tobacco cessation; however, the data are limited. [ 8 39 ]…”
Section: Electronic Nicotine Delivery Systems (Ends) or Electronic CImentioning
confidence: 99%